EVALUATION OF AUTHENTIC ASSESSMENT FOR WRITING SKILL AT JUNIOR HIGH SCHOOLS IN WEST SUMATERA - Sari, Mega Enjela; Zaim, M.; Refnaldi, Refnaldi (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2018)
Evaluation is a process for gathering students’ progress in the learning. Authentic assessment as an evaluation system in 2013 curriculum is needed in assessing students’ process and product of the learning. Yet, teachers need a guidance book in implementing the authentic assessment for assessing students’ writing skill. Those products of authentic assessment have been developed by the experts from Universitas Negeri Padang. This research aimed to evaluate these authentic assessment products for writing skill at junior high schools at the seventh and eighth grade based on the requirement of 2013 curriculum, the content or material, and the authenticity of authentic assessment. To achieve the aims, the research was designed to the evaluation research. The participants of this research were twelve English teachers at junior high schools in West Sumatera and one expert in the language assessment.